Avaliação da função diastólica em portadores de talassemia major - Rodrigues, Alexandre; Guimarães Filho, Fábio Villaça; Braga, João Carlos Ferreira; Rodrigues, Cássia Spínola Custódio; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP] (My University, 2011)
Patients with thalassemia major remain asymptomatic and with preserved ventricular function for a long period of time. However, two basic conditions can be responsible for the commitment of cardiac function in these patients, anemia and hemochromatosis. Recent advances in echocardiography have allowed early identification of ventricular dysfunction caused by hemochromatosis. Moreover, this is an important tool for serial evaluation of these patients, allowing comparisons of structural and cardiac function in different moments.

Portadores de talassemia major (TM) permanecem assintomáticos e com funções ventriculares preservadas por longo tempo, porém, duas condições básicas podem ser responsáveis pelo comprometimento da função cardíaca nesses indivíduos, a anemia e a hemocromatose. Recentes avanços na ecocardiografia possibilitaram a utilização dessa técnica para a identificação precoce de disfunção ventricular secundária à hemocromatose. Além disso, esse exame constitui instrumento valioso para o acompanhamento evolutivo de pacientes, permitindo comparações de variáveis estruturais e funcionais cardíacas em diferentes momentos.
Diastolic function in patients with thalassemia major
Keywords: Echocardiography; Doppler; Hemochromatosis; Thalassemia; Ventricular remodeling; Ecocardiografia doppler; Hemocromatose; Talassemia; Remodelação ventricular